On the culture of material value and the cosmography of riches - Sahlins, Marshall (Instituto de Altos Estudios Sociales, 2016)
Herein is a discourse on value and how economics fails as a science thereof by banishing culture to the status of “exogenous factors.” The argument is demonstrated by an ethnographically informed study of the external origins of riches. Among the conclusions: money (“magical property”) as a means rather than the antithesis of extended kinship; scarcity as a function of value rather than the value of scarcity; and other such contradictions of the deceived wisdom.